The Role of Measurement in the Public Polls (Albanian Case) - Doçi, Fatbardha (European Journal of Multidisciplinary Studies, 2016)
In Albania reality are made a lot of surveys to predict the result of elections. It is so important to have the exactly result of the election of another items to predict. A prestigious company has done the survey in Albania reality, but they have “Forgotten“ that the Albania reality is different from the reality, because they have used the same questionnaires in Albania reality.It is so important to have the right measurement and to have the reliability and the validity of the survey. So we have types of measurement and in my research I have used one of them. If we used the right measurement, we can have a small margin of error and the result of the surveys should be the reliability than the other cases. I have decided to make the survey in Albanian reality lot of survey in two different realities. One of them I have used two kinds of sample, when one of them is systematic sample and another is quota sample. A comparison between two surveys is made providing the same questionnaire (with delicate questions) in the same place and time. The only difference was in the last step of the sample: one of the surveys has made the interviews based on the quota (gender, group age), whereas the other has used the systematic schema (with step – door by door). The margin decided by this way included also the one produced by the used of the quota. The expectation was a determination of differences between answers by this distinction.